Structure-property relations of heterophasic ethylene-propylene copolymers based on a single-site catalyst - M. Aarnio-Winterhof; P. Doshev; J. Seppala; M. Gahleitner (eXPRESS Polymer Letters)
The target of the present study was to investigate the structure-property relationships of heterophasic ethylenepropylene (EP) copolymers based on a single-site (metallocene) catalyst (SSC) supported with an emulsion technology developed by Borealis. The structure of these copolymers, their morphology evolution, as well as resulting mechanical properties were studied by varying the composition of the dispersed phase, i.e. the amorphous ethylene-propylene copolymer or rubber (EPR), in a systematic series of bench-scale products. Next to composition effects, an attempt was made to understand the key differences between products based on Ziegler-Natta catalysts (ZNC) and single-site catalysts (SSC) in terms of polymer structure and property profile. A remarkably different phase morphology with very good phase coupling to the matrix PP and the absence of crystallizable polyethylene in the ethylene-rich copolymers (EPR) was observed for the SSCbased grades, resulting in a high level of impact strength over a wide composition range.